Pembelajaran Berbasis Nilai-nilai Kebangsaan: Suatu Strategi dalam Menangkal Radikalisme di Persekolahan - Rizal Fahmi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The purpose of this research is to investigate the implementation andimpact the program of the ToT Nilai-nilai Kebangsaan Lemhannas RI forteachers and lecturers in West Java Province. Some previous researchesexplained that radicalism growth in the world of schooling in West Java. Fromthe internalization of national values carried out by teachers towards students, itwas formed as an effective strategy as well as a model of deradicalization inschooling. This research was conducted using a qualitative approach. Interviewsand observations were chosen as data collection techniques to obtain deepresults. The results of this research were that the teachers who were alumni of theToT Nilai-nilai Kebangsaan Lemhannas RI generally participate in socializingnational values in learning through varied methods in accordance with thesubjects they are taught. There were differences way or method in implementingnilai-nilai kebangsaan into the course, even though student’s respond wasenthusiast.